2019
DOI: 10.1002/chem.201805936
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Porous Fe3C‐Based Composite Beads as Heterogeneous Oxidation Catalysts

Abstract: A series of multiscale cementite/iron/porous carbon (CIPC‐T) composites with extremely low nitrogen content and millimeter‐size spherical morphology were prepared by simple carbothermal pyrolysis of resin spheres exchanged with ferric oxalate anions. CIPC‐T materials are composed of highly disperse core–shell‐structured Fe3C/Fe@graphitic carbon (CI@GC) nanoparticles embedded in a porous amorphous carbon framework. A mechanism for the formation of the composites is proposed on the basis of the results of XRD, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 74 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…The independent variables coded at three level (− 1, 0, and + 1) and their change ranges were listed in Table 1. The total number of experiments for 17 listed in Table 2 were obtained according to a 3 3 Box-Behnken experimental design (BBD).…”
Section: Ethyl Benzene Oxidation and Test Ethyl Benzene Oxidation Camentioning
confidence: 99%
See 1 more Smart Citation
“…The independent variables coded at three level (− 1, 0, and + 1) and their change ranges were listed in Table 1. The total number of experiments for 17 listed in Table 2 were obtained according to a 3 3 Box-Behnken experimental design (BBD).…”
Section: Ethyl Benzene Oxidation and Test Ethyl Benzene Oxidation Camentioning
confidence: 99%
“…) on TON are concerned, the coefficient value of the quadratic parameter (X 3 2 ) was + 21.80 [Eq. (4)], showing a positive effect of X 3 2 on TON, displaying a greatest synergic effect (synergy), and having a greatest significant effect.…”
mentioning
confidence: 99%
“…Different valent cobalt and PMS would despoil (or lose) an electron, [43] and turned into the corresponding substances. Additionally, metal cobalt also can be oxidized into various valent of cobalt, as per eqn (15)(16)(17)(18). There is no doubt that it would induce the increasing in active ingredients.…”
Section: Full Papermentioning
confidence: 99%
“…However, even though those previously prepared catalysts have demonstrated respectably performance, there is still large room to further enhance efficiency. Modifying the interior nanostructures of materials is favorable for the unlimited accessibility between reactants and active sites . It was shown that the developed interior porosity and enlarged surface area play an important role in efficiency enhancement, considering that the diffusion pathway of the ions/molecules were a determining factor for the whole reaction process .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation